2017
DOI: 10.1534/g3.117.300232
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miRNA-9 Generates Muscle Hypercontraction Through Translational Repression of Troponin-T inDrosophila melanogasterIndirect Flight Muscles

Abstract: MicroRNAs (miRNAs) are small noncoding endogenous RNAs, typically 21–23 nucleotides long, that regulate gene expression, usually post-transcriptionally, by binding to the 3′-UTR of target mRNA, thus blocking translation. The expression of several miRNAs is significantly altered during cardiac hypertrophy, myocardial ischemia, fibrosis, heart failure, and other cardiac myopathies. Recent studies have implicated miRNA-9 (miR-9) in myocardial hypertrophy. However, a detailed mechanism remains obscure. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 85 publications
1
19
1
Order By: Relevance
“…Discrepancies were found between previous studies and our findings regarding the following miRNAs: miR-9a has been reported in embryo development function in D. melanogaster eggs 32 , but in contrast, no significant changes were found in the biological approaches that we used (eggs, females and males); miR-71-5p with overexpression in Manduca sexta (Linnaeus 1763) eggs 39 was in contrast to the expression in males in our findings; miR-10 was overexpressed in D. melanogaster , T. castaneum , Apis mellifera (Linnaeus 1758) and B. germanica eggs 40 , 41 and downregulated in females according to our results. Thus, as explained above, we can infer new and different roles for these miRNAs in Ae.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Discrepancies were found between previous studies and our findings regarding the following miRNAs: miR-9a has been reported in embryo development function in D. melanogaster eggs 32 , but in contrast, no significant changes were found in the biological approaches that we used (eggs, females and males); miR-71-5p with overexpression in Manduca sexta (Linnaeus 1763) eggs 39 was in contrast to the expression in males in our findings; miR-10 was overexpressed in D. melanogaster , T. castaneum , Apis mellifera (Linnaeus 1758) and B. germanica eggs 40 , 41 and downregulated in females according to our results. Thus, as explained above, we can infer new and different roles for these miRNAs in Ae.…”
Section: Discussioncontrasting
confidence: 99%
“…We observed miR-10 and miR-71-5p overexpression in holometabolous and hemimetabolous insects. Only five have been described previously in D. melanogaster embryos playing developmental functions: miR-307 regulated cell death processes through the silencing of wntless 6 ; miR-33 in cell proliferation events by silencing the genes CDK6 y CCND1 31 ; miR-9a in muscle myofibril development by silencing troponin-T 32 ; and miR-9c-5p in the cleaning of unstable maternal transcripts 33 . Finally, miR-iab-4-5p regulating the distribution and development of the wings and halters through the silencing of Ultrabithorax 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This morphological abnormality is suppressed by glial knockdown of HDAC4. In fact, inhibition of glial HDAC4 in these mutants results in an upheld wing phenotype, which occurs in mutants with muscle hypercontraction as a result of altered neuronal excitability (Katti et al, 2017;Montana and Littleton, 2004). Next, we tested if HDAC4 inhibition suppresses neuronal hyperexcitability in the eag,Sh mutant at the larval neuromuscular junction (NMJ).…”
Section: Activation Of the Glial Buffering Program Suppresses Hyperexmentioning
confidence: 99%
“…To monitor mitochondrial and contractile network morphology in the different muscle types in Drosophila , we used the genetically encoded mitochondrial matrix GFP 23 with the UAS-Gal4 system 24 together with F-actin staining (phalloidin). The indirect flight muscles (dorsal longitudinal muscles (DLMs)) in wild-type adult flies showed the characteristic fibrillar contractile phenotype of many individual myofibrils 25, 26 together with many thick, elongated mitochondria interspersed in parallel to the myofibrils (Fig. 1a-d,u).…”
Section: Resultsmentioning
confidence: 99%